DINAMIKA PERADABAN ISLAM PASCA KONFLIK TIMUR TENGAH: Rekonstruksi Identitas Sosial dan Budaya - Sindy Widiarti (LPPM STAI Raudhatul Akmal, 2023)
The prolonged conflict in the Middle East has had a multidimensional impact on Islamic civilisation, particularly in social and cultural aspects. Internal divisions, ideological struggles between sects, and intervention by major countries have complicated geopolitical dynamics and caused the disintegration of the collective identity of Muslims. This study aims to examine the dynamics of Islamic civilisation post-conflict, with a focus on the ongoing process of reconstructing social and cultural identity. Through a descriptive-qualitative approach based on literature review, this study finds that the revival of Islamic civilisation after conflict does not only rely on physical recovery, but also on the strengthening of human values, education, and the revitalisation of inclusive Islamic historical and cultural narratives. The role of the younger generation, diaspora communities, and educational institutions is key to rebuilding a just social order rooted in the principle of rahmatan lil ‘alamin (mercy for all creation). The reconstruction of Islamic civilisation in the post-conflict era is a complex and ongoing process. It requires synergy between the intellectual heritage of the past and the need for social transformation in the present, in order to shape a resilient, tolerant, and adaptive Islamic identity capable of addressing global challenges.